PENGARUH KUALITAS KEPEMIMPINAN, KOMPENSASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN KANTOR DIREKSI PT HUTAHAEAN PEKANBARU - , Nuryanti, Selfia Rahma , Zulfadil (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
This study aims to determine the effect of leadership quality, compensation and job satisfaction on the performance of employees at the director's office of PT Hutahaean Pekanbaru. The population in this study included all employees at the director's office of PT Hutahaean Pekanbaru. Primary data was collected using a questionnaire as an instrument to prove the results of the study. To test the hypothesis in this study, multiple linear regression was used with the help of the SPSS 25 program.The results showed that: 1) there is a positive and significant influence of leadership quality on employee performance at the director's office of PT Hutahaean Pekanbaru, 2) compensation has no effect on the performance of employees at the director's office at PT Hutahaean Pekanbaru, 30 job satisfaction has no effect on the performance of employees at the office of directors of PT Hutahaean Pekanbaru , 4) the quality of leadership, compensation and job satisfaction have a simultaneous effect on the performance of the employees of the directors' office of PT Hutahaean Pekanbaru. Keywords: leadership quality, compensation, job satisfaction, performance